2022
DOI: 10.1155/2022/4753328
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Leak Detection in High Frequency Hydraulic Cylinder Based on Intelligent Control

Abstract: Most of the existing hydraulic cylinder internal leakage detection methods are laboratory testing methods, mainly the pressure-holding method, measurement of hydraulic cylinder settlement method, and measuring cup measurement method. The internal leakage of the hydraulic cylinder affects the damping characteristics of the control system. Therefore, real-time internal leakage detection plays an important role in the control characteristics. This paper first proposes a wavelet analysis-based extraction of hydrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The results showed that CNN outperformed other algorithms. Similarly, Na et al [20] combined wavelet analysis-based feature extraction with CNN to detect leakage.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CNN outperformed other algorithms. Similarly, Na et al [20] combined wavelet analysis-based feature extraction with CNN to detect leakage.…”
Section: Introductionmentioning
confidence: 99%